STABILIZED APPRECIATION. - Sweeney, Henry W. (The Accounting Review, 1932)
If the capital invested in an asset is classified as physical capital, then unrealized "appreciation," which is commonly meant to express the monetary excess of net reproductive cost over net original cost, is all capital. If capital is classified as real capital, then appreciation is capital to the extent of the amount required to express in the current general price level the net original cost of the asset, and the remainder of the appreciation is income. And if capital 18 classified as nominal capital, then the appreciation is all income. Stabilized accounting prefers to restrict the meaning of appreciation to the excess of net reproductive cost over net real cost. If this view is accepted, the orthodox conceptions of appreciation must be rejected. Appreciation becomes converted from unrealized into realized when doubt with respect to its positive existence is dispersed. This happens most often as the result of sale or depreciation of the particular asset. Although the equalized original cost of an asset, and the accumulated depreciation thereon, ought to be shown in some way on the books and financial summaries, the cost of reproduction need not be shown. If, however, as should usually be desirable, it is shown, the excess of the depreciation on reproductive cost over that on real cost is most satisfactorily treated when charged against the unrealized appreciation. But if the depreciation charged to operations must be based upon cost of reproduction, the resulting realized appreciation is, in essence, a correction of current profit and loss although, where necessary, it may satisfactorily be entered in a realized-surplus reserve.